Source and Magma Evolution of the Tuff of Elevenmile Canyon, Stillwater Range, Clan Alpine and Northern Desatoya Mountains, Western Nevada. - Stepner, Daniel (Université d'Ottawa / University of Ottawa, 2017)
The tuff of Elevenmile Canyon (TEC) is a 25.1 Ma trachydacite to rhyolite intracaldera tuff produced by the largest of 6 Oligocene overlapping calderas that, along with related plutons, constitute the Stillwater Caldera Complex, one of the largest eruptions of the Western Nevada Volcanic Field during the mid-Tertiary ignimbrite flare-up. Typically crystal-rich with a mineral assemblage of plagioclase > quartz  sanidine > biotite ± hornblende and clinopyroxene, there are two discernable pumice types throughout the tuff: a lighter crystal-rich pumice and a darker, commonly aphyric pumice type. Rb-Sr and Sm-Nd isotopic compositions of pumice fragments and whole rock samples indicate an enriched mantle component (87Sr/86Srin = 0.70495 – 0.70535, Nd[t=25.1Ma] = -1.13 to -0.39) similar to that of coeval Cenozoic mafic lavas. Pb isotopes (206Pb/204Pbin = 19.042 – 19.168, 207Pb/204Pbin = 15.557 – 15.664) fall along a tight trend between the Northern Hemisphere Reference Line (Hart 1984) and an endmember similar to local granitic units. Major and trace element modelling support a source for the TEC derived from the mixing of anatectic melts of crustal rocks with intruded mantle-derived magmas similar to a local basaltic-andesite.
Keywords: Geochemistry; Isotope Geochemistry; Volcanology; Igneous Systems; Nevada; Ignimbrite